Controlling without owning – owning without controlling: A critical note on two extensions of internalization theory - Forsgren, Mats; Holm, Ulf (Journal of International Business Studies, 2022)
Recent attempts to extend internalization theory into new fields of enquiry illustrate the crucial role of control in the theory. In this paper, we focus on two examples: one applying internalization theory to external business relationships of multinational enterprises (MNEs) and one applying new internalization theory to MNEs’ governance. We argue that, in both cases, the ability of the extended theory to explain MNE behavior can be questioned, either because of the governance of the external relationships is shared between the MNE and its counterparts (as in the first case), or because of the substantial increase in the level of complexity of the MNE’s decision-making system (as in the second case). We conclude that scholars applying internalization theory to MNEs’ external business relationships, and to their decision-making processes, should address what shared governance in external business relationships, and the issue of bounded rationality/bounded reliability, actually mean for the possibility to apply the usual economic logic behind internalization theory. It is essential that future research focuses on what impact the circumscribed control in the two cases has on the ability of MNEs to assess, both ex ante and ex post, the level of transaction costs and managerial costs as bases for its decisions to invest abroad and run foreign operations.